Anal Fistula Human Amniotic Membrane Endosealing (F-HAME): A Proof of Concept Study - Grossi, Ugo; Romano, Maurizio; Rossi, Serena; Gallo, Gaetano; Picciariello, Arcangelo; Felice, Carla; Trojan, Diletta; Montagner, Giulia; Zanus, Giacomo (Frontiers in Surgery, 2022)
The treatment of cryptoglandular anal fistula (AF) is often a challenge for surgeons. Several sphincter-saving procedures have been described as an alternative to fistulotomy, with the common goal of promoting healing and preserve anal continence. The aim of this proof of concept study was to assess the outcomes of human amniotic membrane (HAM) implantation in cryptoglandular transphincteric AF. Two consecutive female were recruited. The primary outcome was clinical healing at 6 months. Secondary outcomes were ultrasonographic healing, complications and reinterventions, AF symptoms, fecal incontinence, psychological impact of treatment, recurrence, development of additional AF, patient satisfaction and quality of life, as measured using validated questionnaires. Both patients (40 and 54-year-old) previously underwent incision and drainage of anal abscess with concomitant seton placement. HAM implantation was performed as a day case under local anesthesia. No intra- or post-procedural complications occurred. Clinical and radiological healing were not achieved at 6 months. However, the external outlet discharge diminished through time, with sustained improvements in quality of life. Clinical healing occurred at 7 months in both patients. Psychological impact of treatment and patient satisfaction were overall good, with improvements in the PHQ-9, GAD-7, and Short Assessment of Patients Satisfaction. HAM implantation is safe and improves patients’ quality of life, progressively leading to clinical healing. Future studies are needed to assess its effectiveness in other etiology of AF.